KARAKTERISTIK FISIKOKIMIA DAN ANTIBAKTERI VIRGIN COCONUT OIL HASIL FERMENTASI BAKTERI ASAM LAKTAT [Physicochemical and Antibacterial Characteristics of Virgin Coconut Oil Fermented with Lactic Acid Bacteria] - Anton Rahmadi; Ipnatul Abdiah; Maya Dewi Sukarno; Titin Purnaningsih (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
Destabilization of oil-water emulsion in coconut milk, in the production of virgin coconut oil (VCO), can be accelerated with the utilization of lactic acid bacteria fermentation. This research was aimed to determine physicochemical and antibacterial characteristics of VCO from coconut hybrid variety fermented with L. casei of Yakult® and two isolates of L. plantarum from mandai (traditionally fermented Artocarpus campeden) and coconut water. The observed physicochemical of VCO included yield, specific gravity, moisture content, saponification value, peroxide value, and free fatty acid. The antibacterial activity was subjected to the well diffusion method against E. coli and S. aureus with chloramphenicol as the positive control. L. casei yielded the best VCO-BAL at 34.5% (v/v), while L. plantarum from mandai and coconut water yielded 29.5% (v/v) and 25.3% (v/v), respectively. VCO-BAL from L. casei had the lightest specific gravity of 0.84±0.04 g.mL-1. Average of measured moisture contents (0.03-0.05%), saponification values (161.3-163.6), peroxide values (0.53-0.86), and free fatty acids (0.11-0.12%) of the three VCO-BALs were not significantly (p>0.05) different with respect to control. VCO-BAL produced from L. plantarum of coconut water did not exhibit better antibacterial activity compared to control. VCO-BAL from L. casei demonstrated highest antibacterial activity against E. coli, 6.45±0.50 mm (58.1% of positive control) and S. aureus, 5.23±0.40 mm (51.3% of positive control). It is deduced that antibacterial activity from VCO-BAL is contributed by hydrophobic bacteriocins.